Asymptomatic renal pseudoaneurysm after percutaneous renal biopsy - Gi Young Yun; Seung Kyo Kim; Seung Kyo Park; Sung Jin Moon; Jung Eun Lee; Suk Won Song; Kwang-Hun Lee; Hyeong-Cheon Park; Sung Kyu Ha; Hoon Young Choi (The Korean Society of Nephrology, 2013)
A 37-year-old man was referred to Division of Nephrology for a new renal cystic lesion that was found on ultrasonography. Four years prior to presentation, a percutaneous renal biopsy had been performed. Computed tomography scan showed a 4.4-cm-sized renal artery pseudoaneurysm in the left kidney. Selective renal angiography revealed a pseudoaneurysm in the left lower pole of the kidney. The renal pseudoaneurysm was successfully embolized with coil. Follow-up Doppler ultrasonography showed no internal blood flow into the aneurysmal sac. His renal function remained stable after coil embolization.